ANALYSIS OF TEMPERATURE FIELDS AT HARDENING OF CONTINUOUSLY-CASTED BIMETALLIC CASTING - E. I. Marukovich; A. M. Branovitski; Ju. A. Lebedinski (Литьë и металлургия, 2006)
The analysis of the temperature fields in a casting and graphite catalyzer at hardening is carried out on the basis of the developed mathematical model of the bimetallic castings continuous horizontal founding process. The dependence of sizes of this zone on temporal and thermophysical parameters of casting is istudied.